A Novel Implementation of Krasnoselskii's Fixed-Point Theorem to a Class of Nonlinear Neutral Differential Equations. (2nd September 2022) - Rezaiguia, Ali; Moumen, Abdelkader; Mennouni, Abdelaziz; Alshammari, Mohammad; Hassan, Taher S.
Abstract : In this work, we examine a class of nonlinear neutral differential equations. Krasnoselskii's fixed-point theorem is used to provide sufficient conditions for the existence of positive periodic solutions to this type of problem.